DIDACTIC POTENTIAL OF MOBILE APPLICATIONS FOR LEARNING ENGLISH AS A FOREIGN LANGUAGE - Blynova Neliia; Kyrylova Oksana; Dolzhenko Maryna (Alfred Nobel University Publisher, 2023)
The article is devoted to the didactic potential of mobile applications for learning English as a foreign language by students of non-philology specialities. Since mobile learning acquires complex and systemic features, it is extremely important to investigate specific means that contribute to the implementation of educational tasks and the acquisition of necessary competencies by students getting higher education. The purpose of the article is to review existing mobile applications designed for learning English as a foreign language by Ukrainian students in order to determine their didactic potential. Research methods: the analysis of sources on the topic of research made it possible to understand the state of development of the topic, the main directions of domestic and foreign research on mobile learning; descriptive provided an opportunity to generalize the experience gained during reconnaissance; synthesis of the obtained data contributed to the conclusion of the research concept and its implementation. The didactic potential of mobile applications in learning English as a foreign language is considered. A number of mobile applications offered by Google Play were analyzed, and it was determined that they can be typologically classified according to various characteristics (age of the target audience, level of foreign language proficiency, developer expertise, amount of processed material, number of downloads and the score with which users rated a certain application). The applications that can be logically and naturally introduced into the educational process of students of the 1st year of the elementary and pre-intermediate levels were analyzed. 8 applications were considered. As a result of the research, it was found out that despite the considerable diversity of the analyzed applications, their common feature is the implementation of the "edutainment" concept, in which educational goals are achieved by combining the game form and the educational component of the material under consideration. Application developers pay the most attention to grammatical material and thematic vocabulary. Learned topics can be consolidated with the help of tests, often presented in a game form. An indisputable positive point is that the studied lexemes, grammatical constructions and whole sentences are voiced by native English speakers. Based on the concept of interval repetition, the developers include tools in the applications that allow students to memorize the material as easily and naturally as possible. These can be, for example: a repetition calendar, a reminder system, associative pictures, quizzes, the ability to create word cards by your own, transcription of words in English, examples of the use of polysemantic lexemes in different meanings, accompanied by translation and voiceover in a male or female voice. Both individual and group work is provided in the applications. The function of group English learning can be easily used during classroom classes. Mobile applications are a powerful resource that a teacher can refer to when dealing with specific topics. It is convenient for the student to use mobile applications outside of class time, consolidating information learned from textbooks and expanding it with the help of material provided in the course. However, mobile applications in no way replace the main textbook, being only one of the varieties of didactic material which is modern, relevant and understandable for a modern student of higher education.